2018
DOI: 10.1111/jai.13856
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on growth, hematology, and immune responses of subadult Chinese sturgeon (Acipenser sinensisGray 1835) under different ammonia nitrogen conditions in recirculating aquaculture system

Abstract: The growth, hematology, and immune responses of subadult Chinese sturgeon (Acipenser sinensis) (avg. wt. 25.11 ± 3.74 kg) were determined at three water temperature levels (12, 18, and 24°C) × three concentrations of total ammonia nitrogen (TAN) (0.05 ± 0.02, 1.03 ± 0.04, and 2.03 ± 0.05 mg/L) for 90 days in recirculating aquaculture system (RAS).At the end of the experiment, all fish were weighed and serum was collected for analysis using biochemical parameters. The temperature level had significant effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Too high an aquaculture density will also increase the rate of oxygen consumption and ammonia excretion of fish, causing oxidative damage, reducing the activities of functional enzymes, disrupting hormone levels, exerting a negative influence on the antioxidant system and immune system of fish (Dediu et al, 2021;Long et al, 2019;Zhang et al, 2019). Besides, a relatively lower stocking density provides low, stable concentrations of ammonia, nitrite, and organic load.…”
Section: Stocking Densitymentioning
confidence: 99%
See 2 more Smart Citations
“…Too high an aquaculture density will also increase the rate of oxygen consumption and ammonia excretion of fish, causing oxidative damage, reducing the activities of functional enzymes, disrupting hormone levels, exerting a negative influence on the antioxidant system and immune system of fish (Dediu et al, 2021;Long et al, 2019;Zhang et al, 2019). Besides, a relatively lower stocking density provides low, stable concentrations of ammonia, nitrite, and organic load.…”
Section: Stocking Densitymentioning
confidence: 99%
“…With the increase of temperature, the antioxidant performance and enzyme activities of fish increase, and the food intake increases until the optimal growth temperature is reached. However, with the increase of temperature beyond the optimum value, the activities of functional enzymes decrease, and the feeding abilities are inhibited, decreasing the growth rate (Abbink et al, 2012; Volkoff & Rønnestad, 2020; Zhang et al, 2019). In addition to directly affecting fish growth, temperature can also affect fish reproduction by affecting gonad maturation time and the reproductive cycle (Davis et al, 2007; Hermelink et al, 2013; Podrabsky et al, 2008; Wuertz et al, 2007).…”
Section: Effects Of Environmental Factors On Rasmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that the growth of sturgeon will be affected under pressure (Hung et al, 1993). When Chinese Sturgeon grew in high density (12.68 kg m −2 ) environment for a long time, its SGR was significantly lower than that in low density (4.80 kg m −2 ) environment (Long et al, 2015), and it shows a similar response under the condition of high temperature or high ammonia nitrogen, that is, the growth rate slows down (Zhang et al, 2019).…”
Section: Hd MD Ldmentioning
confidence: 99%
“…Sturgeons easily adapt to the RAS environment [ 6 ], showing high adjustability regarding a wide range of temperature levels, i.e., 11–26 °C [ 7 , 8 ], and generally tolerating unusual rearing conditions [ 9 ]. The highest sensitivity of sturgeons reared in RAS was noted in terms of oxygen and ammonia levels [ 10 , 11 ]. The general recommendations concerning these parameters are oxygen (D.O.)…”
Section: Introductionmentioning
confidence: 99%